The Original Banana Split: Multi-disciplinary implications of the generation of African and Pacific Plantains in Island Southeast Asia - De Langhe, Edmond; Perrier, Xavier; Donohue, Mark; Denham, Tim Paul (Ethnobotany Research and Applications, 2015)
Traditional starchy banana cultivation in the humid tropics is dominated by two widespread, but geographically discrete, groups of AAB cultivars: plantains in Africa and maoli-popo`ulu in the Pacific. Both AAB subgroups exhibit exceptionally high cultivar diversity due to multiple somatic mutations, and yet both subgroups have relatively similar genetic origins. Although both cultivar groups originated within a region defined by the Philippines, Eastern Indonesia, and New Guinea, the precise area of origin for each AAB group within this region is different. Significantly, the distribution of each sub-group is mutually exclusive: traditional cultivation of maoli-popo`ulu cultivars is not attested to the West of the region and of plantain cultivars to the East. On the basis of botanical data, we argue that the original plantain hybrids were probably formed in the Philippines, while basic maoli-popo`ulu were formed in the Bismarck Archipelago and the Solomon Islands. The generation of these two AAB subgroups shed light on human interactions within Island Southeast Asia before 3000 cal BP, for which there is currently only limited archaeological evidence.